A Study on the Elastoplastic Stable Bearing Capacity of Double-Steering Prestressed Plate Columns - Yanying Li; Bailong Li; Xinsheng Yin; Zhiying Han; Zhipeng Li (Buildings, 2023)
This study investigates the elastoplastic stable bearing capacity of prestressed columns. The end restraint of the novel dual-steering plate brace prestressed column is enhanced, augmenting the efficiency of utilizing steel material. The elastoplastic stable bearing capacity of this new prestressed column is 5.41 times greater than that of a standard non-prestressed column. In contrast, the traditional prestressed columns with identical parameters show only a 2.49 to 3.55 times increase. In addition, this study conducts parameter optimization on the prestressed value, the position of the transverse brace, and the size of the transverse brace in the prestressed column. The buckling load escalates rapidly with an increase in the prestress value within a specific range and then diminishes gradually. The bearing capacity peaks when the transverse brace is positioned at the midpoint. As the size of the transverse brace expands, the load-bearing capacity initially rises linearly and subsequently stabilizes. The findings on the elastoplastic stable bearing capacity and parameter optimization are significantly relevant for practical engineering applications.